Guaianolides from Tanacetopsis karataviensis (Kovalevsk.) Kovalevsk. Issue 7 (3rd April 2022) - Dusmatova, D. E.; Bobakulov, Kh. M.; Turgunov, K. K.; Mukhamatkhanova, R. F.; Uzbekov, V. V.; Gildenast, H.; Englert, U.; Sham'yanov, I. D.; Tashkhojaev, B.; Bruskov, V. P.; Abdullaev, N. D.
Abstract: In continuation of our phytochemical study on the aerial part of Tanacetopsis karataviensis (Kovalevsk.) Kovalevsk, three new guaiane-type sesquiterpene lactones were isolated namely karatanolide (1 ), 11, 13 β -dihydrokaratanolide (2 ) and 11, 13 α -dihydrokaratanolide (3 ), in addition to the two known sesquiterpene lactones 1 β, 10 α -dihydroxyarglabin (4 ) and artefin (5 ). The structures of the isolated sesquiterpene lactones were elucidated by IR and NMR spectroscopy. Single crystal X-ray diffraction allowed to unambiguously confirm the structure of the isolated sesquiterpene lactones. Quantum chemical calculations of the guaianolides 1–3 suggested the existence of two conformations for the seven-membered cycle. All sesquiterpene lactones from Tanacetopsis karataviensis were isolated for the first time. Graphical Abstract: